Characterization and distribution of mechanically competent mineralized tissue in micropores of β-tricalcium phosphate bone substitutes. Issue 3 (April 2017) - Bohner, Marc; Baroud, Gamal; Bernstein, Anke; Döbelin, Nicola; Galea, Laetitia; Hesse, Bernhard; Heuberger, Roman; Meille, Sylvain; Michel, Pascal; von Rechenberg, Brigitte; Sague, Jorge; Seeherman, Howard
Graphical abstract: Abstract : Although bone formation around and within implants has been intensively studied, the role of pores and pore geometry is still debated. Notwithstanding studies reporting the formation of bone and bone components within pores as small as a few micrometers ('micropores'), bone ingrowth is believed to only occur in pores larger than 100 μm ('macropores'). A thorough analysis of 10 different porous β-tricalcium phosphate cylinders (Ø: 8 mm; L: 13 mm) implanted for 2–24 weeks in an ovine model demonstrates ingrowth of mineralized tissue (MT) in pores as small as 1 μm. This tissue contained calcium phosphate, collagen, and interconnected cells. It formed within the first 3–4 weeks of implantation, extended over several hundred micrometers within the ceramic, and contributed to the majority of the early MT formation (including bone) in the defect. The indentation stiffness of the MT-ceramic composite was significantly higher than that of bone and MT-free ceramic. The presented results substantiate the importance of micropores for optimal bone healing, particularly at early implantation times.